2015
DOI: 10.22216/jit.2015.v9i3.416
|View full text |Cite
|
Sign up to set email alerts
|

Efektifitas Metode Preseptor Dan Mentor Dalam Meningkatkan Kompetensi Perawat Klinik

Abstract: Nursing is one profession in the world of health. As the profession is certainly expected that nurses

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 2 publications
0
7
0
6
Order By: Relevance
“…A study was conducted by Binti Ekry Fahrizal (2018) to investigate the contribution of knowledge about triage to Diploma students of nursing in Pekan Baru, it showed that 29.8% of nursing student have poor knowledge of response time triage in Emergency Department [2]. Furthermore, Sulung N. (2015) found that implementation of the competency intervention of the preceptor and mentor methods has a significant effect on the skills of nurses in the Pediatric Ward of RSUP. Dr. M. Djamil Padang [3].…”
Section: Introductionmentioning
confidence: 99%
“…A study was conducted by Binti Ekry Fahrizal (2018) to investigate the contribution of knowledge about triage to Diploma students of nursing in Pekan Baru, it showed that 29.8% of nursing student have poor knowledge of response time triage in Emergency Department [2]. Furthermore, Sulung N. (2015) found that implementation of the competency intervention of the preceptor and mentor methods has a significant effect on the skills of nurses in the Pediatric Ward of RSUP. Dr. M. Djamil Padang [3].…”
Section: Introductionmentioning
confidence: 99%
“…The same thing was mentioned by Norwood (2010), that it is proven to be effective in increasing nurses' perception of their work, increasing their knowledge and skills so that it has an impact on communication and conflict resolution. Research at Dr. RSUP M Djamil Padang also mentioned that mentorship method was effective to improve competency and nurse career development (Sulung, 2016). The development of caring leadership skills can be seen in graph 1 below.…”
Section: Discussionmentioning
confidence: 99%
“…Peran preceptor dalam melaksanakan fungsi supervisi dan edukasi berpotensi menjadi motivasi bagi perawat baru untuk meningkatkan kemampuan berpikir secara kritis. Sulung (2016) berpendapat bahwa seorang perawat baru akan dapat menemukan cara yang unik untuk belajar dan mengembangkan minat secara fleksibel melalui metode preceptorship.…”
Section: Pembahasanunclassified
“…Setiap preceptor mempunyai gaya membimbing yang berbeda meskipun sudah menggunakan formulir yang sama sebagai instrumen untuk mengevaluasi kegiatan pembelajaran pada masa orientasi selama satu bulan. Perlu waktu yang lebih panjang untuk mengevaluasi peningkatan kompetensi setelah selesai dilakukan masa orientasi agar hasil kegiatan pembelajaran selama masa orientasi terhadap kompetensi perawat baru dalam memberikan asuhan keperawatan dapat dinilai secara berkesinambungan (Sulung, 2016).…”
Section: Pembahasanunclassified